Characteristic Strength of Polymer Impregnate Concrete - A., Pavan kumar; kalpana, Ms. (International Journal of Psychosocial Rehabilitation, 2020)
The polymer concrete may be a composite that’s obtained by way of the assimilation of a polymeric material into the concrete matrix. This is regularly helpful in lowering the water-to-cement ratio and improving houses of concrete matrix. Especially this is completed by way of impregnating polymer compound at some point of the concrete blending stage. Here during this study, have a look at it is tried to gauge the behavior of concrete residences with differing varieties of polymers like SBR-Latex, Poly Carboxyl Ether, and Poly Glycol. For this observe M30 grade of concrete mix is ready and carried with differing forms of polymers and complete observe on workability, strength, compaction, flexural electricity has been studied flexural electricity has been studied